Technical analysis and computer trading: Foreign exchange market intervention revisited - Beate Reszat (Intereconomics, 1987)
The efforts of the central banks of Western industrial countries to stabilize exchange rates following the Louvre Agreement demonstrated yet again how difficult it can be to influence events in the foreign exchange markets. What factors are currently affecting exchange rates? What significance attaches to technical analysis in this context?
Keywords: 330; Exchange Rates